If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5)(7x + -1) = a Reorder the terms: (5 + 3x)(7x + -1) = a Reorder the terms: (5 + 3x)(-1 + 7x) = a Multiply (5 + 3x) * (-1 + 7x) (5(-1 + 7x) + 3x * (-1 + 7x)) = a ((-1 * 5 + 7x * 5) + 3x * (-1 + 7x)) = a ((-5 + 35x) + 3x * (-1 + 7x)) = a (-5 + 35x + (-1 * 3x + 7x * 3x)) = a (-5 + 35x + (-3x + 21x2)) = a Combine like terms: 35x + -3x = 32x (-5 + 32x + 21x2) = a Solving -5 + 32x + 21x2 = a Solving for variable 'x'. Reorder the terms: -5 + -1a + 32x + 21x2 = a + -1a Combine like terms: a + -1a = 0 -5 + -1a + 32x + 21x2 = 0 The solution to this equation could not be determined.
| 3b+5b-2b=96 | | K+20=k | | 4x^2-13x+12=3x+6 | | 1996+43x=7385-67x | | 7x^2-5x=-6 | | 14m=13 | | i^29= | | -(8y+4)-(-7y-5)=-6 | | x^2-7-7x=-9x+1 | | 6x^2+31x+5=0 | | x^2-7-7x=-9+1 | | n^2+2n-70=0 | | 3x^2=4.75 | | b^2-14b+49=64 | | (4x-9)(1)=(x-4)ln(5) | | 7385-67x=6250 | | -13.7p=-54.8 | | 38=x-7+2x | | (9+5i)-(6-2i)= | | 4x^2+x+13=9x+10 | | 1996+43x=3200 | | 38=2x-7+x | | 18+14=x | | 18+14= | | 4x^2-17x+17=-2x+3 | | 92=18+x+18+x+x+x | | 10-3x=2(x-1) | | 330=10+x+x | | 3y=5y-30 | | 180=110+24+x+x | | 180=110+24+x | | 2x+8=x+32 |